The impact of asthma and its treatment on growth: an evidence‐based review - Linjie Zhang; Laura Belizario Lasmar; Jose A. Castro‐Rodriguez (Brazilian Society of Pediatrics, 2019)
Objectives: To assess the impact of asthma and its treatment (inhaled corticosteroids and other control medications) on growth. Data sources: The authors searched PubMed (up to August 24, 2018) and screened the reference lists of retrieved articles. Systematic reviews and meta‐analysis were selected. If there was no such article, the authors selected either randomized clinical trials or observational studies. Data synthesis: A total of 37 articles were included in this review. The findings from 21 studies suggest that asthma per se, especially more severe and/or uncontrolled cases, can transitorily impair child's growth. Two Cochrane reviews of randomized clinical trials showed a small mean reduction in linear growth (−0.91 cm/year for beclomethasone, −0.59 cm/year for budesonide, and −0.39 cm/year for fluticasone) in the first year of treatment with inhaled corticosteroids in prepubertal children with persistent asthma. The effects were likely to be molecule‐ and dose‐dependent. A recent review showed that most of "real‐life" observational studies had not found significant effects of inhaled corticosteroids on growth in asthmatic children. Fifteen studies showed that the maintenance systemic corticosteroids could cause a dose‐dependent growth suppression in children with severe asthma, but other controllers (cromones, montelukast, salmeterol, and theophylline) had no significant adverse effects no growth. Conclusions: Severe and/or uncontrolled asthma can transitorily impair child's growth. Regular use of inhaled corticosteroids may cause a small reduction in linear growth in children with asthma, but the well‐established benefits of inhaled corticosteroids in controlling asthma outweigh the potential adverse effects on growth. Use of the minimally effective dose of inhaled corticosteroids and regular monitoring of child's height during inhaled corticosteroids therapy are recommended. Resumo: Objetivos: Avaliar o impacto da asma e seu tratamento (corticosteroides inalados e outros medicamentos de controle) no crescimento. Fontes de dados: Uma busca foi feita no PubMed (até 24 de agosto de 2018) e foram triadas as listas de referência dos artigos recuperados. Revisões sistemáticas e metanálises foram selecionadas. Se não houvesse tal artigo, ensaios clínicos randomizados ou estudos observacionais eram selecionados. Síntese dos dados: Trinta e sete artigos foram incluídos nesta revisão. Os achados de 21 estudos sugerem que a asma por si só, especialmente os casos mais graves e/ou descontrolados, podem prejudicar o crescimento da criança. Duas revisões Cochrane de ensaios clínicos randomizados mostraram uma pequena redução média no crescimento linear (−0,91 cm/ano para beclometasona, −0,59 cm/ano para budesonida e −0,39 cm/ano para fluticasona) no primeiro ano de tratamento com corticosteroides inalados em crianças pré-púberes com asma persistente. Os efeitos pareciam ter efeito dose- e molécula-dependente. Uma revisão recente mostrou que a maioria dos estudos observacionais da "vida real" não encontrou efeitos significativos dos corticosteroides inalados no crescimento de crianças asmáticas. Quinze estudos mostraram que a manutenção de corticosteroides sistêmicos poderia causar uma supressão do crescimento dose-dependente em crianças com asma grave, mas outros controladores (cromonas, montelucaste, salmeterol e teofilina) não tiveram efeitos adversos significativos no crescimento. Conclusões: A asma grave e/ou descontrolada pode prejudicar o crescimento da criança. O uso regular de corticosteroides inalados pode causar uma pequena redução no crescimento linear em crianças com asma, mas os benefícios bem estabelecidos dos corticosteroides inalados no controle da asma superam os potenciais efeitos adversos no crescimento. Recomenda‐se o uso de doses minimamente eficazes de corticosteroides inalados e o monitoramento regular da altura da criança durante a terapia com corticosteroides inalados. Keywords: Asthma, Inhaled corticosteroids, Linear growth, Height, Palavras‐chave: Asma, Corticosteroides inalados, Crescimento linear, Altura